Fetal autopsy: Clinicopathologic correlation in consecutive cases - Shunmuga Priya V; Revathy M; Chandramouleeswari K (Asian Journal of Medical Sciences, 2024)
Background: Fetal and neonatal mortality serves as the most sensitive index of maternal and neonatal care. Congenital malformations remain a common cause of perinatal deaths and account for 10–15% in developing countries. Antenatal anomaly scan has become a standard element of obstetric care and their time for a fetal malformation is about 18 weeks. Fetal autopsy serves as a methodology to confirm the sonogram findings with regard to fetal anomalies. Aims and Objectives: The aim of our present study is to review and evaluate fetal autopsy of stillbirth/fetal losses and to confirm the malformations that were diagnosed by ultrasound. Materials and Methods: A cross-sectional study of a total of 10 cases received during the period of September 2023–October 2023 at the Institute of Obstetrics and Gynaecology. All the cases were spontaneous fetal losses. A standard protocol of autopsy procedure was followed which included external, internal, and histopathological examination. In fetuses with prenatally diagnosed malformations, ultrasound findings were compared with autopsy findings. Results: We analyzed a total of 10 fetuses, which included one chromosomal abnormality, four cardiac anomalies, one multiple anomaly, three central nervous system (CNS) anomalies, and one lethal skeletal dysplasia. The fetal autopsy confirmed the prenatal ultrasound findings in eight cases. Fetuses with CNS abnormality were not appreciated grossly due to early autolysis of the brain in the post-mortem. Conclusion: Prenatal imaging and screening are considered milestone development which detects fetal anomalies. However, the time-tested clinical autopsy which used to be conducted for all hospital deaths to find the cause of death was the norm of yesteryears which threw light on many unidentified causes and many syndromic associations not detected antemortem. Likewise, this case highlights the importance of autopsy correlation with prenatal imaging to highlight the same findings and to detect findings not picked up during imaging.